The Dual Impact of Smartphone Usage on Short-Term Memory, Attention, and Academic Performance in Digital Learning Environments - Anwar , Ch. Mahmood; Hayat, khunsa; Abbas, Hafiz (Sinergi International Journal of Psychology, 2024)
Smartphones have become an integral part of modern education, offering both opportunities and challenges in learning environments. This study explores the impact of smartphone usage on cognitive processes, specifically short-term memory and attention, through a systematic literature review. Utilizing databases such as Scopus, Google Scholar, and PubMed, relevant studies were analyzed to assess the benefits and drawbacks of smartphone integration in education. The findings reveal that structured smartphone use, including gamified learning tools and reinforcement models, enhances engagement and knowledge retention. However, unregulated smartphone use leads to cognitive overload, distractions, and reduced academic performance. The study emphasizes the importance of policy reforms, teacher training, and digital literacy programs to maximize the benefits of mobile technology in education while mitigating its negative effects. Future research should focus on longitudinal studies and cross-cultural comparisons to refine best practices for smartphone-assisted learning. The results underscore the need for balanced technology integration to optimize learning outcomes in an increasingly digitalized academic landscape.